PENGEMBANGAN E-MODUL IPS SD BERBASIS KONTEKSTUAL MATERI MENGHARGAI PENINGGALAN SEJARAH DI LINGKUNGAN SETEMPAT - Akhmadi, Mochammad Noor; Rufi'i, Rufi'i; Hartono, Hartono (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2021)
Creating effective learning is one of the teacher's tasks. Effective learning can be achieved if teachers are able to prepare material programmatically, choose and determine learning methods that are in accordance with the material being taught, and evaluate learning outcomes. One of the teaching materials in electronic form is e-module. E-Modul is one of the learning tools that can facilitate student learning because it contains clear objectives, subject matter, activity sheets and can check student understanding. The absence of an e-module about material respecting historical heritage in the local environment at Plumbungan Elementary School and the incompatibility of the content of learning materials with the environment where students live makes researchers motivated to develop contextual-based SD social studies e-modules so that learning objectives can be achieved. This study uses the Borg & Gall research model, researchers modify the development stage to be simpler. The data analysis technique used is descriptive quantitative analysis and descriptive qualitative. This research has produced a product in the form of a contextual-based elementary social studies e-module for grade IV on material respecting historical heritage in the local environment. Based on the results of the study, it can be concluded that the e-module developed in this study is categorized as valid, interesting, practical, and effectively used in learning. Valid is illustrated from the results of the validator's assessment that all validators state good results in both aspects, namely material and language. Interesting is illustrated from the student's assessment during small group trials and field trials. Practically illustrated from the student response questionnaire after the field trial that all students can use the e-module well. The results of the development are also classified as effective as seen from student learning activities and teacher activities in the learning process increase.